My student exchange experiences: a cultural perspective - Isnin, Nadrawina (Universiti Teknologi MARA, Sarawak, 2006)
The article describes the writer’s experience joining a student/teacher exchange programme between Stockholm University and Universiti Kebangsaan Malaysia. During several overseas trips, the writer observed different cultures such as the kindness of Japanese people, the discipline of Singaporeans, the nationalism of Thai people, and the beautiful environment in Switzerland. The writer was impressed by the Japanese people’s good time management, respect for other cultures, and their awareness of halal food for Muslim participants. The writer also noticed the high level of safety in Japan. In Switzerland, the writer admired the honesty of the Swiss people, such as a flower stall where customers could take flowers and leave money without supervision. These experiences reminded the writer of the importance of honesty and values taught in Islam.